FTIR, FT Raman and UV-Visible Spectral Measurements and Analysis on Atorvastatin Calcium - GUNASEKARAN, S.; RENUGA DEVI, T.S.; SAKTHIVEL, P.S. (Asian Journal of Chemistry, 2010)
Atorvastatin calcium is the drug of choice in allopathic medicine for the treatment of hyperlipidemia and mixed dyslipidemia. In the present study, the infrared, Raman and UV-Vis spectroscopic measurements are employed for the qualitative analysis of atorvastatin calcium. The different functional group vibrations present in the compound are identified and assigned satisfactorily using the FTIR and FT Raman spectra. The UV-Vis spectral measurements carried out on the compound identify the wavelength maxima λmax. By exposing the drug to various environmental conditions, the qualitative change in the behaviour of the drug is tested by employing internal standard calculations. The interaction of the compound with some trace elemental constituents such as sodium, potassium, calcium, iron and lead have been analysed by employing UV-Vis spectral measurements.